2018
DOI: 10.4171/jems/799
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and the structure of large character sums

Abstract: Let M (χ) denote the maximum of | n≤N χ(n)| for a given non-principal Dirichlet character χ (mod q), and let N χ denote a point at which the maximum is attained. In this article we study the distribution of M (χ)/ √ q as one varies over characters (mod q), where q is prime, and investigate the location of N χ . We show that the distribution of M (χ)/ √ q converges weakly to a universal distribution Φ, uniformly throughout most of the possible range, and get (doubly exponential decay) estimates for Φ's tail. Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…Proof. Let R = (log q) 3 , and apply Dirichlet's theorem to obtain integers r and k satisfying 1 k N/R, (r, k) = 1 and…”
Section: Preliminary Estimates For Character Sumsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Let R = (log q) 3 , and apply Dirichlet's theorem to obtain integers r and k satisfying 1 k N/R, (r, k) = 1 and…”
Section: Preliminary Estimates For Character Sumsmentioning
confidence: 99%
“…Concerning long character sums, Hildebrand [16] has shown that if χ(−1) = 1 then |S(χ, αq)| < εq 1/2 log q, for all α ∈ (0, 1) except for a set of measure q −c 1 ε and that if α = o(1) and χ(−1) = 1 then S(χ, αq) = o(q 1/2 log q). [1] and Bober, Goldmakher, Granville and Koukoulopoulos [3] have obtained much more precise results concerning the distribution of long character sums and Granville and Soundararajan [13] have obtained results concerning the distribution of short character sums. Granville and Soundararajan [14] have also shown that…”
Section: Introductionmentioning
confidence: 99%
“…Proof of Theorem 1.2. Let z = (log Q) 5 and let 2 y (log Q) 3/2 be a real number to be chosen later. Then, by Proposition 2.4, it follows that for all but at most Q 1/2 primitive characters χ (mod q) with q Q,…”
Section: Youness Lamzourimentioning
confidence: 99%
“…In a recent work, Bober et al [5] studied the distribution of large values of M(χ) as χ varies over non‐principal characters modulo q, where q is a large prime. Among their results, they showed that the bounds in (1.7) are the best possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation